FORMULATING INSIGHTS ON JOB SATISFACTION AND ITS IMPACT ON JOB PERFORMANCE IN MALAYSIA’S PUBLIC SECTOR - Yusuff, Mohd Azhar Mohd; Shokory, Suzyanty Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study aims to explore the factors that influence job satisfaction and its impact on job performance among civil servants in Malaysia. Using a qualitative approach with a Basic Qualitative Inquiry design, data were obtained through semi-structured interviews with five participants from various public sector departments. The findings revealed that job satisfaction was influenced by supportive leadership, task success, recognition, and benefits provided to employees. In addition, project success motivated employees to enhance their performance. However, challenges such as frequent policy changes, management instability, and lack of recognition negatively affected motivation and commitment. Recognition also emerged as a cross-cutting theme, influencing both satisfaction and performance depending on its presence or absence. This study contributes to the literature by offering new insights into the relationship between job satisfaction, organizational commitment, and job performance in the public sector. Practical suggestions include introducing clear KPIs, meaningful reward systems, and professionalism courses to strengthen satisfaction and performance. The study also highlights the need for more systematic management and a more appreciative approach to foster a productive work environment.